ROLE OF MOLECULAR FEACHURES OF GASTRIC CANCER (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
The aim of our study to analyse the results of tumor microenviron in patients with gastric cancer. According to the results of our analysis of the pre-collected literature and independent research, the con-clusions of the molecular examination in gastric cancer and information on the microenvironment of the tumor have shown that it is possible to control the disease at any stage.